ORIENTASI KONSUMEN, OPORTUNISME KONSUMEN, PERJANJIAN KONTRAKTUAL, KOMITMEN SUMBER DAYA DAN KEMAMPUAN REVERSE LOGISTIC - Yaqoub, Amak Mohamad; Indriani, Nurfitri (Jurnal Manajemen dan Kewirausahaan, 2014)
This research aimed to investigate the relationship between reverse logistic capabilities with customer orientation, customer opportunism, resource commitments and contractual arrangements and investigate the relationship between reverse logistic capabilities and cost saving. Data from 30 respondents were collected using questionnaire then analyzed using SmartPLS. Hypotheses testing indicated the absence of relationship between customer orientation and reverse logistic capability. Research also found that resource commitment and contractual arrangement have positive relationship with reverse logistic capability, while negative relationship empirically proven on the relationship between reverse logistic capability and cost saving.